May Measurement Month 2018: an analysis of blood pressure screening results from Malaysia. (28th August 2020) - Chia, Yook Chin; Ching, Siew Mooi; Devaraj, Navin Kumar; Chew, Bee Nah; Ooi, Pei Boon; Mohamed, Mohazmi; Othman, Azli Shahril; Kang, Pei San; Husin, Hanis Saadah; Mohamad Gani, Abdul Hafiz; Hamid, Dalyana; Beaney, Thomas; et al.
Abstract: Hypertension continues to be the top global killer, contributing to over 10 million deaths annually. As prevalence and unawareness of hypertension remain high in Malaysia, this study was aimed to screen more individuals to identify those with undiagnosed hypertension. Respondents aged ≥18 years were recruited through opportunistic sampling at various screening sites including health clinics, hospitals, student health centres, universities, community halls, shopping malls, as well as through other health screening campaigns. Each respondent completed a questionnaire on socio-demographic, environmental, and lifestyle data. Anthropometric measurements as well as three blood pressure (BP) measurements were obtained from all participants. Hypertension was defined as a systolic BP ≥140 mmHg and/or diastolic BP ≥90 mmHg or taking antihypertensive medication. The total number of participants was 4866. The mean age of the participants was 39.8 (17.6) years with 61.1% female participants. Of the 4866 participants, 1405 (28.9%) had hypertension. The proportion of those aware of their hypertension status was 76.3% (1073/1405). The proportion of those with hypertension on medication was 71% (998/1405). Of those receiving antihypertensive treatment, 62.4% (623/998) had controlled BP. The proportion of hypertension in this study was 28.9%. The awareness rate of 76.3% compares favourably to a previously reported national level of 43.2%. Hence, BP screening programmes may be effective at increasing awareness and should be conducted annually.